Inhaled ciclesonide for outpatient treatment of COVID-19 in adults at risk of adverse outcomes: a randomised controlled trial (COVERAGE). (July 2022) - Duvignaud, Alexandre; Lhomme, Edouard; Onaisi, Racha; Sitta, Rémi; Gelley, Ambre; Chastang, Julie; Piroth, Lionel; Binquet, Christine; Dupouy, Julie; Makinson, Alain; Lefèvre, Benjamin; Naccache, Jean-Marc; et al.
Abstract: Objectives: To assess the efficacy of inhaled ciclesonide in reducing the risk of adverse outcomes in COVID-19 outpatients at risk of developing severe illness. Methods: COVERAGE is an open-label, randomized controlled trial. Outpatients with documented COVID-19, risk factors for aggravation, symptoms for ≤7 days, and absence of criteria for hospitalization are randomly allocated to either a control arm or one of several experimental arms, including inhaled ciclesonide. The primary efficacy endpoint is COVID-19 worsening (hospitalization, oxygen therapy at home, or death) by Day 14. Other endpoints are adverse events, maximal follow-up score on the WHO Ordinal Scale for Clinical Improvement, sustained alleviation of symptoms, cure, and RT-PCR and blood parameter evolution at Day 7. The trial's Safety Monitoring Board reviewed the first interim analysis of the ciclesonide arm and recommended halting it for futility. The results of this analysis are reported here. Results: The analysis involved 217 participants (control 107, ciclesonide 110), including 111 women and 106 men. Their median age was 63 years (interquartile range 59–68), and 157 of 217 (72.4%) had at least one comorbidity. The median time since first symptom was 4 days (interquartile range 3–5). During the 28-day follow-up, 2 participants died (control 2/107 [1.9%], ciclesonide 0), 4 received oxygen therapy at home and were not hospitalized (control 2/107 [1.9%], ciclesonide 2/110 [1.8%]), and 24 were hospitalized (control 10/107 [9.3%], ciclesonide 14/110 [12.7%]). In intent-to-treat analysis of observed data, 26 participants reached the composite primary endpoint by Day 14, including 12 of 106 (11.3%, 95% CI: 6.0%–18.9%) in the control arm and 14 of 106 (13.2%; 95% CI: 7.4–21.2%) in the ciclesonide arm. Secondary outcomes were similar for both arms. Discussion: Our findings are consistent with the European Medicines Agency's COVID-19 task force statement that there is currently insufficient evidence that inhaled corticosteroids are beneficial for patients with COVID-19.